Pedagogía Museística: vínculo entre arte, educación y curaduría en el Museo de Sitio Manuel Chávez Ballón de Machupicchu - Baca Cussi, Angela Maitté (2023)
The research work carried out proposes to establish the principles to develop a Museum Pedagogy in the “Manuel Chávez Ballón” Site Museum of Machupicchu, with a new perspective that links art, education and curatorship, associated with a new approach to museology current. With the purpose that the museum can identify with a more socially responsible cultural institution, since it has the potential to negotiate cultural borders and become an agent of social change, and thus create contact areas where identities and collections, people and objects can discover new possibilities for personal and social life The research was carried out at the “Manuel Chávez Ballón” Site Museum of Machupicchu, as its name indicates, it is a site museum due to the theme and archaeological material recovered in situ, its sole purpose being to explain and broadcast the highlights of the place. Initially it was inaugurated by the Departmental Board of Archeology of Cusco on August 13, 1966 and on July 25, 2005, with a new museum and museum script it was reopened. The qualitative research was carried out with the use of two investigative instruments: the survey of national and foreign museum visitors and the semi-structured interview with the museum staff, and the data was collected deductively The museum meets its three objectives which are conservation, research and dissemination, which are the main functions of a museum, it does not include the educational function, therefore the museum would be considered as a traditional nineteenth-century museum, closed in character and not as a current museum, open to the community since it must be understood that the educational function must be a priority in the politics, organization and operation of museums, within the conception of heritage-museum education. The main results are that the Implementation of Museum Pedagogy is the means that allows promoting new possibilities in the teaching and learning processes at the Manuel Chávez Ballón Site Museum, with the interest of contributing to educational action and thus converting the museum in a space of interaction, generator of experiences of diversity of dialogues and new knowledge that is created from contact with space, with objects and exhibitions. The development of Museum Pedagogy would be obtained by linking art (allows INTERPRETATIVE experiences through theatrical visits in the museum and didactic films with contents of the scientific research carried out on the archaeological collections that the museum protects), education (allows BUILDING MEANING and become familiar with the museum's cultural material, through didactic workshops, temporary exhibitions, traveling exhibitions, conferences) and curatorship (management of collections through the registration, inventory and cataloging of movable cultural property to GIVE ACCESS to the public and create the catalog in line).